The Protection Law to Consumers for The Right to Get Information from Imported Product - Berlian; Permai Yudi (LEGAL BRIEF, 2022)
The existence of a free market, makes the faucet of commerce between countries wide open. Business actors are increasingly competing to produce highly competitive goods and services. It is expected to be able to compete on a global scale. Here consumers will get a better and wider choice. However, consumers may not get their legal rights as consumers, due to various things that happen. So in this context, the presence of Law Number 8 of 1999 which regulates consumer protection is more of a legal effort to provide protection, and is not intended at all to kill the business of entrepreneurs. In trade between countries, where foreign products can enter freely into the country, the government needs to be present to advocate for its citizens. The state plays an active role in controlling the interaction between business actors and potential consumers, which in this context is information on imported products. The right of consumers to know information regarding goods imported from foreign countries must be fulfilled, so that disputes are avoided. So furthermore, the presence of the Consumer Dispute Resolution Agency is certainly an important thing that is very beneficial for both parties, namely business actors and consumers, when they are involved in business interactions that lead to conflict.